Risk Factors for Venous Thromboembolism in Patients with Chronic Liver Disease. (March 2013) - Walsh, Kelly A; Lewis, Daniel A; Clifford, Timothy M; Hundley, Jonathan C; Gokun, Yevgeniya; Angulo, Paul; Davis, George A
BACKGROUND: Pharmacologic prophylaxis for venous thromboembolism (VTE) in patients with chronic liver disease (CLD) presents a unique challenge because of coagulopathies associated with the disease. When evaluating whether these patients require VTE prophylaxis upon hospitalization, it would be advantageous if risk factors for the development of VTE in this population were known. OBJECTIVE: To evaluate risk factors associated with the development of VTE in patients with CLD. METHODS: A retrospective case-control study was conducted. Patients admitted to the University of Kentucky Chandler Hospital from October 2006 to July 2010 with a diagnosis of CLD and VTE were matched in a 1:3 fashion with CLD patients without VTE. The primary objective was to determine whether there were significant differences in laboratory values between the 2 groups. RESULTS: During this time, 27 patients with CLD (1.0%) were diagnosed with VTE. These patients had significantly lower median aspartate aminotransferase (AST) (47 vs 70 U/L, p = 0.04), alanine transaminase (ALT) (24.5 vs 36 U/L, p = 0.02), albumin (2.1 vs 2.4 g/dL, p = 0.02) and hematocrit (Hct) (28.3% vs 32%, p = 0.03) values compared to the control patients. Patients with albumin lower than 1.9 g/dL had a 5.1 times greater risk of VTE compared to patients with albumin of 2.8 g/dL and higher (OR 5.14, 95% CI 1.05–25.2). CONCLUSIONS: Patients with CLD who developed VTE had significantly lower AST, ALT, albumin, and Hct compared to those of control patients. Studies are necessary to further examine the significance of this finding.